Investigating the determinants of customer loyalty at Kedai Kopi Kulo in Jakarta - Aurelia, Evelyn; Ruslim, Tommy Setiawan (Nur Science Institute, 2025)
The food and beverage industry in Indonesia experienced significant growth, driven by changes in urban lifestyles, including the rising popularity of coffee consumption across generations. Kedai Kopi Kulo, despite its initial success during its early establishment, faced challenges as evidenced by a decline in its Top Brand Index from 2020 to 2024. This decline was suspected to be linked to decreasing levels of customer loyalty. This study evaluated the influence of service quality, price fairness, and store atmosphere on customer loyalty, with customer satisfaction serving as a mediating variable. The research adopted a quantitative approach using a cross-sectional survey of 205 respondents selected through purposive sampling. Data analysis was conducted using SEM-PLS. The findings revealed that price fairness and store atmosphere had a positive and significant impact on customer satisfaction, which in turn affected customer loyalty. However, service quality did not significantly influence either variable. These results provided strategic insights for Kedai Kopi Kulo, emphasizing the importance of focusing on price fairness and store atmosphere to enhance customer loyalty.